Geography of hospital admissions for multiple sclerosis in England and comparison with the geography of hospital admissions for infectious mononucleosis: a descriptive study. Issue 6 (6th January 2011) - Ramagopalan, Sreeram V; Hoang, Uy; Seagroatt, Valerie; Handel, Adam; Ebers, George C; Giovannoni, Gavin; Goldacre, Michael J
Abstract : Objective: It is well recognised that variation in the geographical distribution of multiple sclerosis (MS) exists. Early studies in England have shown the disease to have been more common in the North than the South. However, this could be an artefact of inaccurate diagnosis and ascertainment, and recent data on MS prevalence are lacking. In the present study, data were analysed to provide a more contemporary map of the distribution of MS in England and, as infectious mononucleosis (IM) has been shown to be associated with the risk of MS, the geographical distribution of IM with that of MS was compared. Methods: Analysis of linked statistical abstracts of hospital data for England between 1999 and 2005. Results: There were 56 681 MS patients. The admission rate for MS was higher in females (22/10 5 ; 95% CI 21.8 to 22.3) than males (10.4/10 5 ; 95% CI 10.2 to 10.5). The highest admission rate for MS was seen for residents of Cumbria and Lancashire (North of England) (20.1/10 5 ; 95% CI 19.3 to 20.8) and the lowest admission rate was for North West London residents (South of England) (12.4/10 5 ; 95% CI 11.8 to 13.1). The geographical distributions of IM and MS were significantly correlated (weighted regression coefficient (r (w))=0.70, p<0.0001). Admission rates for MS were lowest in the area quintile with the highest level of deprivation and they were also lowest in the area quintile with the highest percentage of population born outside the UK. A significant association between northernliness and MS remained after adjustment for deprivation and UK birthplace. Conclusions: The results show the continued existence of a latitude gradient for MS in England and show a correlation with the distribution of IM. The data have implications for healthcare provision, because lifetime costs of MS exceed £1 million per case in the UK, as well as for studies of disease causality and prevention.